Polycrystalline apatite synthesized by hydrothermal replacement of calcium carbonates - Kasioptas, A.; Geisler, T.; Perdikouri, C.; Trepmann, C.; Gussone, N.; Putnis, Andrew (2011)
Aragonite and calcite single crystals can be readily transformed into polycrystalline hydroxyapatite pseudomorphs by hydrothermal treatment in a (NH4)2HPO4 solution. Scanning electron microscopy of the reaction products showed that the transformation of aragonite to apatite is characterised by the formation of a sharp interface between the two phases and by the development of intracrystalline porosity in the hydroxyapatite phase. In addition, electron backscattered diffraction (EBSD) imaging showed that the c-axis of apatite is predominantly oriented perpendicular to the reaction front with no crystallographic relationship to the aragonite lattice. However, the Ca isotopic composition of the parent aragonite, measured by thermal ionization mass spectrometry was inherited by the apatite product.Hydrothermal experiments conducted with use of phosphate solutions prepared with water enriched in 18O (97%) further revealed that the 18O from the solution is incorporated in the product apatite, as measured by micro-Raman spectroscopy. Monitoring the distribution of 18O with Raman spectroscopy was possible because the incorporation of 18O in the PO4 group of apatite generates four new Raman bands at 945.8, 932, 919.7 and 908.8cm-1, in addition to the ?1(PO4) symmetric stretching band of apatite located at 962cm-1, which can be assigned to four 18O-bearing PO4 species. The relative intensities of these bands reflect the 18O content in the PO4 group of the apatite product. By using equilibrated and non-equilibrated solutions, with respect to the 18O distribution between aqueous phosphate and water, we could show that the concentration of 18O in the apatite product is linked to the degree of 18O equilibration in the solution. The textural and chemical observations are indicative of a coupled mechanism of aragonite dissolution and apatite precipitation taking place at a moving reaction interface.